Etnobotani pembuatan inoknson oleh Suku Byak - Maturbongs, Rudi Aprianto; Kafiar, Lies M; Pono, Wahyudi (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Byak Indigenous people use Inoknson (noken) as a source of income apart from making houses, machetes, and boats. System of knowledge and art in the life circle of the Biak people understand Inoknson as a medium of communication and expression of life that is lived collectively because it is closely related to the functions, symbols, and meanings of symbols of each Inoknson type and size. The study aimed to identify species of plants used as raw material for inoknson, describes raw material extraction, drying, dyeing, and waving process, as well as the conservation status of the selected plant species. The descriptive method with participatory observation and interview techniques is employed in this research. The results showed Inoknson raw materials are from the inner barks of three species namely: Warmas (Melochia umbellata), Mandwes (Juncus effusus), and Anfan (Hibiscus tiliaceus). The Warmas is more the preferred raw material because it is stronger and more durable. The IUCN 2022 conservation status of the three plant species is the Least concern. The process of making Inoknson starts from taking raw materials, peeling and cleaning the barks, drying the fibers, separating and forming fibers, coloring and weaving Inoknson, and marketing. The transfer of knowledge about inoknson only delivers to women, from mother to daughter or to their relatives interested. Warmas raw materials are collected from the surrounding secondary forest, carried out at a certain time, by collecting from three plants with a diameter of 10-20 cm with a height of ± 2 meters. This method is one of the traditional conservation concepts carried out by the Byak tribal community in maintaining and conserving the raw materials of inoknson.